Cryogenic Exfoliation of Non‐layered Magnesium into Two‐Dimensional Crystals. Issue 26 (21st May 2019) - Zhang, Chen; Xu, Yingfeng; Lu, Ping; Wei, Chenyang; Zhu, Chenxi; Yao, Heliang; Xu, Fangfang; Shi, Jianlin
Abstract: Physical exfoliation of layered precursors is one of the most prevailing techniques to prepare two‐dimensional (2D) crystals, which, however, is considered to be intrinsically inapplicable to non‐layered bulks. Now, plane cleavage differentiation is identified in metallic magnesium at cryogenic temperature (CT), and a cryogenic exfoliation strategy of non‐layered magnesium into 2D crystals is developed. The cleavage anisotropy of the Mg lattice in response to the external mechanical stress originates from the CT‐induced specific inactivation of basal slip, which results in the basal cleavage perpendicular to c axis. The exfoliated novel 2D Mg crystals exhibit remarkable localized surface plasmon resonances, holding great promise for the applications in harvesting and converting solar energy. Beyond creating a new member for the burgeoning 2D family, this study may provide a useful tool for the physical exfoliations of various non‐layered materials. Abstract : Revealing the layers : Based on the identification of the cryogenic temperature‐induced specific inactivation of basal slip in a metallic Mg lattice, which results in cleavage anisotropy in response to the external mechanical stress, non‐layered magnesium with directionless metallic bonds could be physically exfoliated into 2D crystals at cryogenic temperature.